Presence of contractile impairment appears crucial for structural remodeling in idiopathic left bundle-branch block - Salatzki, Janek; Wilhelm, Theresa Rita; Riffel, Johannes; André, Florian; Hirschberg, Kristóf; Ochs, Andreas; Hund, Hauke; Müller-Hennessen, Matthias; Giannitsis, Evangelos; Friedrich, Matthias; Scholz, Eberhard P.; Frey, Norbert; et al. (Journal of cardiovascular magnetic resonance, 2021)
To differentiate effects of ventricular asynchrony from an underlying hypocontractile cardiomyopathy this study aimed to enhance the understanding of functional impairment and structural remodeling in idiopathic left bundle-branch block (LBBB).